Analysis of compliance of waste classification with Ukrainian legislation and EU directives - Bryk, Anastasiia; Korniienko, Iryna; Yastremska, Larysa; Kuznietsova, Olena; Baranovskyy, Mikhaylo; Monchenko, Olena; Chernenko, Yana (Problems of Environmental Biotechnology, 2024)
Analysis of compliance of waste classification with Ukrainian legislation and EU directives